Outreach to Science Faculty and Students Through Research Exhibitions. - Tina Chan; Chris Hebblethwaite (Issues in Science and Technology Librarianship, 2014)
Penfield Library at the State University of New York at Oswego (SUNY Oswego) has a gallery exhibit space near the front entrance that is used to showcase student-faculty research and art class projects. This article features the library's outreach efforts to science faculty and students through research exhibitions. The library held an exhibition for science research posters in Fall 2012 and Spring 2014. Requests were sent to science faculty inviting them to feature their student-faculty research posters in the library. The first request received 13 posters; the second request received 14. Research posters were displayed in the gallery exhibit space and inside the library cafe. We also discuss the hanging system used to display the posters. Having research posters displayed in the library in a visible, central, and active location, provided greater visibility to the broader campus community to view the latest research from science students and faculty. [ABSTRACT FROM AUTHOR]